Relasi FPI dengan Dayah dalam Penegakan Syari’at Islam di Aceh - Zahlul Pasha Karim (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2020)
This article attempts to answer why FPI's relationship with Dayah in Aceh is so close. This condition is seen in contrast to several other areas in Indonesia that are seen to experience frequent collisions. This article shows that the relations between FPI and Dayah groups in Aceh occurred for several reasons: first, the FPI organization in Aceh was led by Dayah people and used the Dayah santri network as a mass base. When FPI entered Aceh, the idea was rejected by some senior Acehnese scholars. After FPI succeeded in approaching young people from the Dayah circles, such as Muslem Attahiry, FPI's progress was seen to be very strong and succeeded in establishing its influence in some Dayah. Second, FPI in Aceh has the right space on the issue they are raising, namely Islamic Syari'at. Politicians who need an image of taking sides with shari'ah need to use FPI, either directly or indirectly. Third, the character of Acehnese people who are fanatical and like religious symbols so they don't care less about FPI's background. The people of Aceh will accept it as long as they (FPI) wrap their actions and agendas with narratives and religious symbols.